The Growth and Yield of Local Upland Rice (Oryza sativa L.) Wakawondu Cultivar in Various Plant Populations and Balanced Fertilization - La Ode Afa; Azhar Ansi; Zulfikar Zulfikar; Muhidin Muhidin; Alan Al Qadri (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2022)
The present study aimed to analyze the effect of plant population and fertilization based on efficiency and nutrient adequacy balanced between organic and inorganic on the growth and yield of local upland rice Wakawondu cultivar. The treatment design was split-plot in a randomized block design with three replications. The main plot was the number of seeds per planting hole (A) consisting of three levels, namely one seed (A1), two seeds (A2), and three seeds per planting hole (A3). Subplots were organic and inorganic fertilization (B) which consists of four levels, namely without fertilization (B0), 100% bokashi from Cromolaena odorata or 10 tons ha-1 (B1), giving 100 % inorganic fertilizer or Urea 200 kg ha-1, SP-36 100 kg ha-1, KCl 100 kg ha-1 (B2), and a combination of 50% bokashi fertilizer or 5 tons ha-1, and 50% inorganic fertilizer or Urea 100 kg ha-1, SP-36 50 kg ha-1, KCl 50 kg ha-1 (B3). Plant height, number of leaves, leaf area, productive and maximum of tillers, harvesting age, flag leaf area, length of panicle, total number of grains, percentage of open grain, grain weight of 1000 grains, dry grain weight, and yield were the variables observed. Data were statistically analyzed using ANOVA and further DMRT α= 0.05. The results showed that three seeds per planting hole were the best treatment to increase the number of productive tillers, namely 7.8 tillers with a production of 1.52 tons ha-1 or an increase in productivity by 5% compared to one seed per planting hole. A balanced fertilization combination of organic and inorganic fertilizers is the best treatment that can increase the number of productive tillers, namely 7.1 tillers with a production of 1.8 tons ha-1 or an increase in productivity of 16% compared to without fertilization.